1995
DOI: 10.1007/bf00705647
|View full text |Cite
|
Sign up to set email alerts
|

Pathway analysis of radiation-sensitive meiotic mutants ofCoprinus cinereus

Abstract: We have isolated 37 radiation-sensitive mutants of the basidiomycete Coprinus cinereus. Each mutation is recessive, and the collection defines at least ten complementation groups for survival of gamma irradiation. Four complementation groups define the genes rad3, rad9, rad11 and rad12, which are required both for survival of gamma irradiation and for meiosis. Mutants in each of these four groups fail to complete meiosis and produce mushrooms with greatly reduced numbers of viable spores. Propidium iodide stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 53 publications
2
30
0
Order By: Relevance
“…Other studies report defects in premeiotic DNA replication and meiotic prophase I, but the majority of defects appear to be localized at the stage of meta-anaphase I (216,389,396,397,405,435,466,498,502,538,539,542). From ␥-radiation-sensitive mutants exhibiting defects in chromosome condensation and synapsis in meiosis, an epistasis group of rad3-9-11-12 has been defined (405,498,538,542). The first genes involved in meiosis and DNA repair (rad9, rad11/mre11, and spo11) have been isolated by mutant complementation and by a two-step, semirandom PCR recovering DNA inserts of a REMI mutant ( (101,130,539,542).…”
Section: Mutant Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies report defects in premeiotic DNA replication and meiotic prophase I, but the majority of defects appear to be localized at the stage of meta-anaphase I (216,389,396,397,405,435,466,498,502,538,539,542). From ␥-radiation-sensitive mutants exhibiting defects in chromosome condensation and synapsis in meiosis, an epistasis group of rad3-9-11-12 has been defined (405,498,538,542). The first genes involved in meiosis and DNA repair (rad9, rad11/mre11, and spo11) have been isolated by mutant complementation and by a two-step, semirandom PCR recovering DNA inserts of a REMI mutant ( (101,130,539,542).…”
Section: Mutant Analysismentioning
confidence: 99%
“…Two other genes act in sterigma formation following meiosis, 13 genes are involved in prespore formation, and 4 genes contribute to nuclear migration into the spores (214). Other studies report defects in premeiotic DNA replication and meiotic prophase I, but the majority of defects appear to be localized at the stage of meta-anaphase I (216,389,396,397,405,435,466,498,502,538,539,542). From ␥-radiation-sensitive mutants exhibiting defects in chromosome condensation and synapsis in meiosis, an epistasis group of rad3-9-11-12 has been defined (405,498,538,542).…”
Section: Mutant Analysismentioning
confidence: 99%
“…Nipped-B encodes a member of a highly conserved protein family, which includes Scc2 and Mis4 of S. cerevisiae and S. pombe, discovered in screens for factors that control sister chromatid cohesion (Furuya et al 1998;Michaelis et al 1997), C. cinereus Rad9 identified in a screen for factors required for deoxyribonucleic acid (DNA) repair and meiosis (Valentine et al 1995), and human Nipped-B-Like (NIPBL/delangin), mutated in Cornelia de Lange syndrome (CdLS; Krantz et al 2004;Tonkin et al 2004). Nipped-B family proteins contain seven HEAT repeats implicated in protein-protein interactions (Neuwald and Hirano 2000), and NIPBL missense mutations in all seven cause CdLS Miyake et al 2005;Deardorff and Krantz, personal communication).…”
Section: Introductionmentioning
confidence: 99%
“…The members of the Mre11 complex have been grouped by epistasis analysis (Game et al 1980;Malone and Esposito 1981;Ivanov et al 1992;Ajimura et al 1993;Valentine et al 1995) and have been shown to directly interact ( Johzuka and Ogawa 1995;Petrini et al 1995;Dolganov et al 1996;Trujillo et al 1998;Varon et al 1998). Mammalian deletion mutants of the Mre11 complex exhibit embryonic lethality (Xiao and Weaver 1997;Luo et al 1999;Yamaguchi-Iwai et al 1999;Zhu et al 2001).…”
mentioning
confidence: 99%
“…C. cinereus has naturally synchronous meiosis (Raju and Lu 1970), well-developed cytogenetics (Pukkila et al 1984;Pukkila and Lu 1985;Seitz et al 1996;Li et al 1999), and an annotated genomic sequence (Stajich et al 2006). In screens for mutants defective in both the survival of gamma radiation and meiosis (Zolan et al 1988;Valentine et al 1995), we identified four complementation groups, termed rad3, rad9, rad11, and rad12. These four genes are all part of the same gamma radiation survival pathway (Valentine et al 1995;Cummings et al 2002).…”
mentioning
confidence: 99%